Cinematographic proposal, “Ben-ji al poder”, result of master’s degree in creative writing workshops at San Marcos University - Bustamante Estela, Samuel (2021)
The article addresses the world of cinema and audiovisual language as contemporary instruments of communication and education. It briefly indicates the process followed in the development of a film script, and how it was applied in the writing of the Ben-ji al power script, achieved thanks to the Master's in Creative Writing workshops at the National University of San Frames. Likewise, a literary and theological analysis of the text that inspires the theme of the film is highlighted, and brushstrokes are given about the finished work of the script about the human values of power and self-denial, written by Samuel Bustamante Estela (hereinafter Samuel Bustamante).